Divergência genética e seleção de cultivares de feijão de diferentes tipos de grãos baseada em caracteres de arquitetura de planta, produtividade de grãos e qualidade tecnológica - Kläsener, Greice Rosana (2020)
Currently, there is a greater demand for common bean cultivars (Phaseolus vulgaris L.) of different types of grains with superior traits for plant architecture, grain yield and technological quality of grains. Therefore, the objectives of this work were: (1) to evaluate whether common bean cultivars of different types of grains differ for the plant architecture, grain yield and technological quality traits; (2) study the correlations between these traits; (3) to analyze the genetic divergence between cultivars; and (4) select the common bean cultivars that stood out for these traits. For this, 22 common bean cultivars of different types of grains were evaluated for the plant architecture, grain yield and technological quality traits, in two growing seasons, in the experimental area of the Plant Science Department of the Federal University of Santa Maria, Santa Maria/RS. The experimental design used was randomized blocks, with three replicates. The data obtained were submitted to individual and combined analyzes of variance. The Scott-Knott test, at 5% probability, was applied to cluster the cultivars. Associations between traits were studied using Pearson's linear correlation, in the mean of the environments. Genetic divergence was assessed by principal component analysis, Tocher's method, canonical variables and mean link between groups (UPGMA), to form groups with similar traits. The rank sum and multiplicative selection indexes were used for the simultaneous selection for plant architecture and grain yield and for technological quality traits. In the analysis of variance, significant differences were observed for genotype, type of grain, environment and genotype x environment interaction for most of the trait under study. In general, intermediate to high magnitude correlation estimates between plant architecture and technological quality traits were obtained. In the analysis of principal components, the length of the second internode and the length of the first internode were determinant in the formation of the groups. By Tocher's method, the groups were formed based on different traits of plant architecture and grain yield. The analysis by canonical variables and UPGMA clustered the cultivars according to the luminosity of the grains. The cultivars BRS Campeiro, Guapo Brilhante and BRS Esteio were selected by the selection index based on rank sum, due to the higher average grain yield, and the cultivars BRS Radiante and Hooter, by the traits associated with upright plant architecture. These cultivars must be selected by the breeding program and used in controlled hybridizations. The cultivars BRS Executivo, BRSMG Realce, Hooter, IPR Tiziu, BRS Esteio and Guapo Brilhante were selected by the multiplicative index, as they present desirable color, medium to large-sized grains and fast-cooking.